An insight into Cadmium poisoning and its removal from aqueous sources by Graphene Adsorbents. Issue 1 (2nd January 2019) - Mudila, Harish; Prasher, Parteek; Kumar, Mukesh; Kapoor, Himanshu; Kumar, Anil; Zaidi, Mohammad Gulham Haider; Verma, Amit
ABSTRACT: Graphene alone, in modified form or its composites had find their explicit position in the field of adsorption technology and hence assist in detection and removal of heavy metals like Cd (permissible limit 0.1 mg/L), which can cause various physiological problems if entered in variety of biota. Attributed to their unique physiognomies graphene-based adsorbent had classed themselves superior as compared to other carbonaceous adsorbent like CNT's or activated carbon, etc. This assessment summarizes the validity of graphene and its composite as a superior adsorbent for decontamination of Cd from aqueous environment; in addition, this evaluation also pronounces the toxicity profile of trace graphene and necessity of regeneration of the adsorbent.